2014
DOI: 10.1021/ja501530n
|View full text |Cite
|
Sign up to set email alerts
|

C2H2 Treatment as a Facile Method to Boost the Catalysis of Pd Nanoparticulate Catalysts

Abstract: A facile method to boost the catalysis of Pd nanoparticulate catalysts by simple C2H2 treatment is developed. During the C2H2 treatment, Pd nanoparticles serve as active catalysts to polymerize C2H2 into trans-polyacetylene. The deposition of trans-polyacetylene layer on Pd nanoparticles makes their surface hydrophobic. Such a hydrophobic surface modification helps to accumulate more hydrophobic substrates during catalysis, making the modified Pd nanoparticulate catalysts more active than untreated catalysts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 43 publications
(56 reference statements)
5
60
0
Order By: Relevance
“…It has been reported that the monolayer obtained by the reaction of alkynes with hydroxyl‐terminated surfaces shows a higher stability compared to that obtained by the reactions of silanes, phosphonates, and alkenes . The contact angles of water droplets on TNA were measured to verify the change in their surface hydrophilicity . As shown in Figure b, the contact angle on the nanotube arrays changed from 0° to 14° after the PA treatment, implying that TNA became more hydrophobic.…”
Section: Resultsmentioning
confidence: 91%
“…It has been reported that the monolayer obtained by the reaction of alkynes with hydroxyl‐terminated surfaces shows a higher stability compared to that obtained by the reactions of silanes, phosphonates, and alkenes . The contact angles of water droplets on TNA were measured to verify the change in their surface hydrophilicity . As shown in Figure b, the contact angle on the nanotube arrays changed from 0° to 14° after the PA treatment, implying that TNA became more hydrophobic.…”
Section: Resultsmentioning
confidence: 91%
“…The resulting coated-nanostructures where surprisingly more active in the hydrogenation of styrene than their naked counterparts [100].…”
Section: Modelling the Kinetics And The Diffusion Process In Capped Nmentioning
confidence: 97%
“…Zheng et al . obtained a surface hydrophobic Pd catalyst by depositing trans‐polyacetylene layer on Pd nanoparticles . This modified catalyst showed higher activity than the unmodified catalyst in the hydrogenation of styrene and nitrobenzene.…”
Section: Figurementioning
confidence: 99%